2014
DOI: 10.7235/hort.2014.12226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Soil Amendments on Establishment Vigor, Seedling Emergence, and Top Growth in Kentucky Bluegrass

Abstract: Due to limited supplies and expensive importing costs, it is a goal to replace overseas peat with local soil amendments in turf industry of Korea. The study was initiated to compare the performances of five domestic and imported organic soil amendments (OSAs) on establishment characteristics and to provide basic information for root zone composition on sports turf design and construction. The study was conducted in Kentucky bluegrass (Poa pratensis L., KB) under greenhouse conditions from March to June in 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The organic matter content of soil should range from 1% to 3% to increase the soil's water-holding capacity. According to Kim [21], organic matter improves soil structure, aeration, moisture content, nutrient availability and ecosystem longevity. Adams and Saxon [22] observed that excessive organic matter content in the root zone leads to macropore blockage and deterioration in the physical properties of soil, including drainage, aeration and water retention, which can restrict root formation and increase susceptibility to disease.…”
Section: Resultsmentioning
confidence: 99%
“…The organic matter content of soil should range from 1% to 3% to increase the soil's water-holding capacity. According to Kim [21], organic matter improves soil structure, aeration, moisture content, nutrient availability and ecosystem longevity. Adams and Saxon [22] observed that excessive organic matter content in the root zone leads to macropore blockage and deterioration in the physical properties of soil, including drainage, aeration and water retention, which can restrict root formation and increase susceptibility to disease.…”
Section: Resultsmentioning
confidence: 99%